Sociodemographic characteristics of pediatric patients with vascular malformations: Results of a single site study - Mohnasky, Michael; Brondon, Jennifer; Lee, Sang Yub; Kim, Kyung Rae (Frontiers in Pediatrics, 2023)
Vascular malformations, the abnormal development of blood vessels, are a rare set of congenital anomalies. The sociodemographic factors associated with vascular malformations in pediatric patients are poorly understood. This study examined sociodemographic factors of 352 patients presenting to a single vascular anomaly center from July 2019 to September 2022. Characteristics such as race, ethnicity, sex, age at presentation, degree of urbanization, and insurance status were recorded. This data was analyzed by comparing the different types of vascular malformations, including arteriovenous malformation, capillary malformation, venous malformation (VM), lymphatic malformation (LM), lymphedema, and overgrowth syndrome. Patients were primarily white, not Hispanic or Latino, female, had private health insurance, and were from the most urban setting. No differences in sociodemographic factors were found among the different vascular malformations except patients with VM presented at a later age than patients with LM or overgrowth syndrome. This study provides novel insight into the sociodemographic factors of pediatric patients presenting with vascular malformations and indicates a need for their improved recognition for the timely initiation of treatment.